Kualitas Pelayanan Mobil Unit Penerangan pada Dinas Pengendalian Penduduk dan Keluarga Berencana Kabupaten Sumedang - Dhesti Widya Nurhasanah Ningrum; Novi Fitriani; Arip Rahman Sudrajat (Universitas Medan Area, 2019)
The purpose of this study is to measure the quality of service of Mobil Unit Penerangan in the Dinas Pengendalian Penduduk dan Keluarga Berencana of Sumedang Regency. This study uses a type of qualitative research with two sources of data used, namely primary data and secondary data. The informants in this study were four people who were Advocacy and KIE field employees. Data was obtained through literature studies and field studies. Data processing is carried out through a process of data reduction, data presentation, and examination of conclusions or verification. The results of the study show that the service quality of Mobil Unit Penerangan is quite good. This can be seen from the quality of operational vehicles and inadequate service equipment, providing services that are not timely, and not meeting the needs of the community well for information on Keluarga Berencana programs. The suggestions for research are the need for the addition of infrastructure and operators for Mobil Unit Penerangan, and the regular training in information technology provided to service personnel so that services can be completed quickly and accurately.